Benefits and safety of myomectomy during cesarean section - Kusuma, Anak Agung Ngurah Jaya (Universitas Airlangga, 2024)
HIGHLIGHTS 1. Myomectomy during cesarean section is a recommended and safe procedure. 2. This procedure benefits the patient because it avoids a second operation and anesthesia complications and is cost-saving. ABSTRACT Uterine myoma is a tumor in the uterus that is generally benign. There are many types of uterine myomas. These tumors can grow on the outer wall of the uterus, on the uterine muscle, or it can also be on the inner wall of the uterus. The most frequent kind of uterine tumor is myoma. Uterine myoma mostly occurs in women over thirty years of age. Its prevalence ranges from 5.4% to 77%, with uterine fibroids accounting for up to 5% of pregnancies. The myomectomy procedure is an option for women who still want children but are concerned about the possibility of subsequent surgical intervention. The myomectomy cesarean section is indicated if there were complications related to the myoma in a previous pregnancy. It also avoids the possibility of repeat laparotomy for fibroid removal in the future. Myomectomy surgery should be planned based on fibroids' location, size, and quantity, using suitable imaging. Myomectomy cesarean section can be an option compared to cesarean section without myomectomy, especially if it is performed by experienced surgeons with proper hemostatic techniques and performed in tertiary-level health facilities. This article discusses the details of the benefits and safety of myomectomy during cesarean section so that it might be considered before performing this procedure.